Analisis Kandungan Logam Berat Pb dan Cd pada Siput Gonggong (Strombus sp) di Perairan Kecamatan Bukit Bestari - Khairil Anam; Fadhliyah Idris; Agung Dhamar Syakti (Universitas Tribhuwana Tunggadewi, 2019)
This research is to determine the Pb and Cd heavy metal content in Strombus sp and waters of Bukit Bestari District, Tanjungpinang City, Riau Islands Province. The method of this research is purposive sampling method. The instrument used to determine the Pb and Cd heavy metal content is AAS (Atomic Absorption Spectrophotometry). The results of the study showed that the Pb content in seawater at stations I, II, III was 0.611 mg / L, 0.563 m / L, 0.595 mg / L . The results obtained in sediments at stations I, II, III are 10,488 mg / kg, 8,376 mg / kg, 10,052 mg / kg. The results found on Strombus sp at stations I, II, III were 1,975 mg / kg, 1,275 mg / kg, 1,031 mg / kg. For research results on Cd in Strombus sp at stations I, II, III are 0.036 mg / kg, 0.035 mg / kg, station 0.031 mg / kg. The value obtained is the average results obtained from each sub station.